PERFORMANCE OF BARANGAY NUTRITION SCHOLAR IN BRGY. 171: BASIS FOR CAPABILITY PROGRAM (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Child malnutrition continues to be a major global health concern, with significant consequences that affect individuals, families, and entire nations. Beyond the immediate health risks to children, malnutrition influences wider societal outcomes by limiting educational success, reducing labor productivity, and slowing economic development. Its long-term impacts include poor cognitive and physical development and greater vulnerability to illness, all of which collectively obstruct a nation’s ability to thrive and advance. To gather accurate and meaningful data for the study, the researcher employed a survey questionnaire as the primary instrument. The checklist-style questionnaire was designed to comprehensively address all aspects of the research problem and respond to the specific questions stated. It was developed by the researcher using insights from relevant literature and previous studies. A single set of questionnaires was prepared and distributed to the respondents. A survey assessing the performance of Barangay Nutrition Scholars revealed generally positive results across four key areas: training, engagement, empowerment, and work environment. Respondents expressed strong agreement regarding the effectiveness of their training and the sense of empowerment they experienced. They also reported a strong sense of belonging and achievement in their work environment. However, slightly lower ratings were observed in areas related to the training's impact on job satisfaction and the level of participation in engagement initiatives. Overall, the findings indicate that the scholars are performing well and feel positively about their roles. To improve the performance of Barangay Nutrition Scholars, the following key recommendations are suggested: enhance training programs to improve job satisfaction and effectiveness; strengthen engagement initiatives through a variety of meaningful activities; and provide more flexible workload management to prevent burnout. Additionally, fostering a supportive and inclusive work environment, addressing challenges such as limited resources and community resistance, and investing in capacity-building efforts are vital. Tailored communication strategies and the implementation of continuous monitoring and feedback systems are also crucial for achieving sustainable performance and long-term success.
Keywords: barangay nutrition scholars; training programs; employee engagement; workload management; inclusive work environment; capacity building; communication strategies; performance improvement; monitoring; feedback mechanisms